Zakat As a Corporate Social Responsibility: How Does It Affect the Financial Performance of Islamic Banks? - Ali, Muhammad Ahmar; Shuib, Mohd Sollehudin; Mat Nor, Alias (University of Jordan, 2023)
Islamic banks should actively engage in Corporate Social Responsibility (CSR) activities as part of their moral obligations to contribute to society and surroundings. This study aims to investigate the influence of Zakat contribution, as a proxy of CSR, on the financial performance of Islamic banks in Malaysia. The study used panel-data analysis, whereby the annual reports of 11 local Islamic banks in Malaysia were analyzed over a ten• year period from 2010 to 2019. Fixed- and random-effect regression model analyses were conducted to analyze the results of the study. The findings reveal that there is a positive and significant relationship between Zakat contribution and the financial performance proxied by Return on Asset (ROA) and Return of Equity (ROE) of the Islamic banks in Malaysia. Hence, the findings of the study confirmed the importance of social elements, like Zakat, in the operations of Islamic banks, as well as in the banks' performance